MCO in Malaysia: consumer confidence and households’ responses - Siti 'Aisyah Baharudin; Hayyan Nassar Waked; Mohd Shah Paimen (Penerbit Universiti Kebangsaan Malaysia, 2021)
This research attempts to analyze households' responses to Movement Control Orders (MCO) and assess the impact of MCO on consumer confidence based on the potential disproportionate impact on various income groups in Malaysia. Households' responses and consumer confidence are measured through an online survey to collect the targeted groups' financial situation and household information and expectations during MCO. A total of 660 respondents from all over Malaysia were involved in this study. Analysis of the MCO responses showed that households were able to comply with MCO rules with the highest positive response of 99.7%. In comparison, the households' responses to the implementation of MCO showed the highest negative response of 18.4%, with the majority represented by the B40 income category (65.2%). The consumer confidence present index is operating at six times higher than the expectation index, which indicates that the implementation of MCO in the short-run has a moderate impact on households' economic status than in the long-run involving the COVID-19 pandemic effect on the overall economy. According to the people's confidence to the government in the long-run, current political developments are essential to influence the people's confidence in the economy. The consumer confidence index gives an overview of two policies that need to be emphasized by the government. Based on the short-run status of food consumption, this study strongly recommends that the policymakers consider establishing a National Food Stockpile in light of the nation's food security and moving on to food-based agriculture that considers the targeted groups in the long-run.